ANALISIS IMPLEMENTASI ENTERPRISE RESOURCE PLANNING (ERP) DALAM MENINGKATKAN EFISIENSI PENGELOLAAN KEUANGAN PERUSAHAAN - Obert Sean; Alfin Alfin; Steven Lim; Dorie P. Kesuma (CV. Denasya Smart Publisher, 2026)
This study aims to evaluate the impact of Enterprise Resource Planning (ERP) implementation on the effectiveness of financial management in companies. The research uses a qualitative approach through a literature study by collecting secondary data from journals, books, and previous studies. The variables examined include ERP implementation and financial management effectiveness, with indicators such as process speed, data accuracy, system integration, and ease of information access. The results indicate that ERP implementation has a positive impact on the effectiveness of financial management, including faster financial reporting processes, reduced recording errors, and easier real-time access to information. In addition, ERP supports better integration and collaboration among company divisions. However, ERP implementation also faces several challenges, such as high investment costs, system complexity, and the need for user training. This study is expected to serve as a reference for understanding the benefits and challenges of implementing ERP in corporate financial management.